Advances in breeding for high grain zinc in rice - Swamy, B.P. Mallikarjuna; Rahman, Mohammad Akhlasur; Inabangan-Asilo, Mary Ann; Amparado, Amery; Manito, Christine; Chadha-Mohanty, Prabhjit; Reinke, Russell; Slamet-Loedin, Inez H. (Springer, 2016)
Zinc (Zn) is one of the most essential micronutrients required for the growth and development of human beings. More than one billion people, particularly children and pregnant women suffer from Zn deficiency related health problems in Asia. Rice is the major staple food for Asians, but the presently grown popular high yielding rice varieties are poor supplier of Zn in their polished form. Breeding rice varieties with high grain Zn has been suggested to be a sustainable, targeted, food-based and cost effective approach in alleviating Zn deficiency. The physiological, genetic and molecular mechanisms of Zn homeostasis have been well studied, but these mechanisms need to be characterized from a biofortification perspective and should be well integrated with the breeding processes. There is a significant variation for grain Zn in rice germplasm and efforts are being directed at exploiting this variation through breeding to develop high Zn rice varieties. Several QTLs and gene specific markers have been identified for grain Zn and there is a great potential to use them in Marker-Assisted Breeding. A thorough characterization of genotype and environmental interactions is essential to identify key environmental factors influencing grain Zn. Agronomic biofortification has shown inconsistent results, but a combination of genetic and agronomic biofortification strategies may be more effective. Significant progress has been made in developing high Zn rice lines for release in target countries. A holistic breeding approach involving high Zn trait development, high Zn product development, product testing and release, including bioefficacy and bioavailability studies is essential for successful Zn biofortification